2021
DOI: 10.1108/bepam-03-2021-0054
|View full text |Cite
|
Sign up to set email alerts
|

Assessing design buildability through virtual reality from the perspective of construction students

Abstract: PurposeThe purpose of this paper is to evaluate the impact of visual models on the ability of construction students to assess design buildability.Design/methodology/approachThe study engaged 45 construction students from one selected tertiary education institute in New Zealand. The data collection process involved meeting the students face-to-face and demonstrating the VR model to them, after which the students completed an online questionnaire and assessed design buildability using both 2D drawing and virtual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…Therefore, promoting the benefits of earth buildings, not only for individuals but for the environment, is crucial to gaining support for these buildings. According to Nikolić and Whyte [25] and Samarasinghe and Piri [26], using modern technology such as virtual reality is a more effective way to promote earth buildings as it shifts the attitudes and mindsets of individuals.…”
Section: The Lack Of Awareness Of Earth Buildingsmentioning
confidence: 99%
“…Therefore, promoting the benefits of earth buildings, not only for individuals but for the environment, is crucial to gaining support for these buildings. According to Nikolić and Whyte [25] and Samarasinghe and Piri [26], using modern technology such as virtual reality is a more effective way to promote earth buildings as it shifts the attitudes and mindsets of individuals.…”
Section: The Lack Of Awareness Of Earth Buildingsmentioning
confidence: 99%
“…Improving buildability in construction has been the interest of many researchers (e.g. Samarasinghe and Piri, 2022;Singhaputtangkul and Low, 2015;Lam and Wong, 2009;Lam et al, 2006;Wong et al, 2006b). However, there have been no studies that focus on the roles of clients in buildability improvement in Nigerian construction projects.…”
Section: Introductionmentioning
confidence: 99%
“…The existing literature on buildability is extensive (Osuizugbo et al. , 2022a, b, c; Samarasinghe and Piri, 2021; Osuizugbo, 2020a; Shim et al. , 2019; Li et al.…”
Section: Introductionmentioning
confidence: 99%
“…, 2006b, Mbamali et al., 2005; Low, 2001) and it has focused particularly on developed countries. In recent time for example, the studies by Samarasinghe and Piri (2021) found out that virtual reality models have significant benefits for assessing design buildability in New Zealand. Osuizugbo (2020a) reported that studies on buildability carried out in developing countries are limited.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation